2012
DOI: 10.1308/147363512x13311314195376
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Fluids: Do Doctors Know What They are Prescribing ?

Abstract: fluid prescription is an essential part of peri-operative care in surgical patients. This is usually left to the most junior trainees. Although knowledge of fluid prescription is part of the core curriculum in all undergraduate and most postgraduate exams, junior doctors may still lack sufficient knowledge and training to perform this competently. Prescription is therefore variable and often inappropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…6,[15][16][17][18][19] Surgical SpRs and consultants perform slightly better than their juniors but little is known about the knowledge of 'senior medical' clinicians. 20 In postoperative surgical patients, junior clinicians are responsible for >85% of fluid prescriptions. 1,3,20 However, in medical practice, middle grade clinicians (eg SpRs) often 'direct' fluid management, which is subsequently 'written up' by junior colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,[15][16][17][18][19] Surgical SpRs and consultants perform slightly better than their juniors but little is known about the knowledge of 'senior medical' clinicians. 20 In postoperative surgical patients, junior clinicians are responsible for >85% of fluid prescriptions. 1,3,20 However, in medical practice, middle grade clinicians (eg SpRs) often 'direct' fluid management, which is subsequently 'written up' by junior colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…20 In postoperative surgical patients, junior clinicians are responsible for >85% of fluid prescriptions. 1,3,20 However, in medical practice, middle grade clinicians (eg SpRs) often 'direct' fluid management, which is subsequently 'written up' by junior colleagues. In an 'apprenticeship-style' training system, like GIM, inadequate senior clinician 'knowledge' is likely to impact junior colleagues training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of consultant surgeons in 2002 revealed that only 16% of respondents believed their pre-registration house officers were adequately trained and only 30% thought the fluids prescribed were adequate [8]. Subsequent studies have continued to show that FY1s have a poor knowledge base for fluid prescribing [9][10][11][12][13][14], with patients often given too much fluid with an excess of sodium and not enough potassium. Furthermore, fluid assessments are commonly performed without reference to the fluid balance or the latest biochemistry results [1,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the type and quantity of fluids prescribed and the implications they have on patient morbidity [1,15]. They have consistently recommended improvement in junior doctor education 1 1 [7,8,10,[12][13][14][15]], yet fluid prescriptions still remain highly variable [13,14]. This study explores the nature of fluid reviews during the out-of-hour periods (OOHs) to determine if additional improvements could be made by addressing how and when fluid reviews are requested.…”
Section: Introductionmentioning
confidence: 99%